The influence of an artificial playing surface on injury risk and perceptions of muscle soreness in elite Rugby Union - Williams, S.; Trewartha, G.; Kemp, S. P. T.; Michell, R.; Stokes, K. A. (Scandinavian Journal of Medicine & Science in Sports, 2016)
This prospective cohort study investigated the influence of an artificial playing surface on injury risk and perceptions of muscle soreness in elite English Premiership Rugby Union players. Time loss (from 39.5 matches) and abrasion (from 27 matches) injury risk was compared between matches played on artificial turf and natural grass. Muscle soreness was reported over the 4 days following one match played on each surface by 95 visiting players (i.e., normally play on natural grass surfaces). There was a likely trivial difference in the overall injury burden relating to time-loss injuries between playing surfaces [rate ratio = 1.01, 90% confidence interval (CI): 0.73-1.38]. Abrasions were substantially more common on artificial turf (rate ratio = 7.92, 90% CI: 4.39-14.28), although the majority of these were minor and only two resulted in any reported time loss. Muscle soreness was consistently higher over the 4 days following a match on artificial turf in comparison with natural grass, although the magnitude of this effect was small (effect sizes ranging from 0.26 to 0.40). These results suggest that overall injury risk is similar for the two playing surfaces, but further surveillance is required before inferences regarding specific injury diagnoses and smaller differences in overall injury risk can be made.